Detection of Rotavirus in Stool Samples of Gastroenteritis Patients - Román, Enid; Martínez, Idalí (Puerto Rico Health Sciences Journal, 2005)
In this pilot study, we examined 100 stool samples from patients with gastroenteritis to determine the presence of Rotavirus using immunoassays and molecular diagnostic methods. When the samples were analyzed by enzyme-linked immunoabsorbent assay (ELISA), we found 11 Rotavirus-positive samples. However, using molecular techniques (reverse transcriptase-polymerase chain reaction (RT/PCR]), we identified 51 positive samples for Rotavirus. These results corroborate the generally accepted concept that molecular techniques are more sensitive than serological diagnostic tests. In addition, our data suggests that Rotavirus is an important etiologic agent of gastroenteritis in the local pediatric population. More extensive studies are necessary to determine the prevalence of Rotavirus in Puerto Rico in order to design effective control measures to protect our population against this pathogen.